Implementasi Peraturan Derah Kabupaten Karanganyar Nomor 4 Tahun 2021 Tentang Penyelenggaraan Perlindungan Anak Dalam Rangka Menjamin Dan Melindungi Hak Anak di Kabupaten Karanganyar (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This research aims to understand and analyze the implementation of a Regional Regulation related to the Organization of Child Protection in Karanganyar Regency and the factors that hinder the Organization of Child Protection in Karanganyar Regency. The type of research used is empirical research. The nature of this research is descriptive with an approach based on data obtained from a source or focused interview and a legislative approach or statute approach. The type of data used includes primary and secondary legal materials. The data collection techniques used in this research include surveys through document study methods, interviews, and observations. Primary data is collected by studying related legislation and regulations as legal materials and conducting observations and interviews with sources as research objects, while secondary data is collected through literature studies of scientific books, law journals, theses, dissertations, legal articles, and legal materials relevant to this legal research. The results of the research show that the implementation of a Regional Regulation related to the Organization of Child Protection serves as legal protection that acts as a guarantee to provide justice and legal certainty for children, especially in protecting children's rights. The obstacles in the Organization of Child Protection in Karanganyar Regency are due to the handling being based on community reports and the lack of education, understanding, and knowledge of the community regarding Karanganyar Regency Regional Regulation Number 4 of 2021 on the Organization of Child Protection, which is caused by limited funds for its implementation.